Metode Pembelajaran Gramatika Bahasa Arab (Telaah Buku Al-Lubab Quantum Reading Book Karya Ahmad Fakhruddin) - Slamet Mulyani (STAIN Bengkalis, 2020)
Arabic Grammar is often considered a scourge by the majority of students. This condition has finally received serious attention from various Arabic language activists by presenting a lot of solutions so that students are easy and happy to learn Arabic. This article aims to evaluate the book Al-Lubab Quantum Reading Book by KH. Ahmad Fakhruddin using Mackey's theory. The results of this study are expected to be a recommendation to the author of the book and other authors in compiling a textbook. All data were collected through the documentation method for further analysis and presented through a qualitative descriptive approach. Based on data analysis, it is known that Al-Lubab's book has fulfilled the selection and presentation elements but is still very weak in the aspects of gradation and repetition. Thus, it is recommended that textbook writers should pay attention to all aspects so the material can be studied and understood easily by students.